HIV-1 Treatment Failure, Drug Resistance, and Clinical Outcomes in Perinatally Infected Children and Adolescents Failing First-Line Antiretroviral Therapy in Western Kenya. (1st February 2022) - Nyandiko, Winstone; Holland, Sabina; Vreeman, Rachel; DeLong, Allison K.; Manne, Akarsh; Novitsky, Vladimir; Sang, Festus; Ashimosi, Celestine; Ngeresa, Anthony; Chory, Ashley; Aluoch, Josephine; Orido, Millicent; et al.
Abstract : Background: Long-term impact of drug resistance in perinatally infected children and adolescents living with HIV (CALWH) is poorly understood. We determined drug resistance and examined its long-term impact on failure and mortality in Kenyan CALWH failing first-line non-nucleoside reverse transcriptase inhibitor–based antiretroviral therapy (ART). Setting: Academic Model Providing Access to Healthcare, western Kenya. Methods: Participants were enrolled in 2010–2013 (timepoint 1) and a subsample re-enrolled after 4–7 years (timepoint 2). Viral load (VL) was performed on timepoint 1 samples, with genotyping of those with detectable VL. Primary endpoints were treatment failure (VL >1000 copies/mL) at and death before timepoint 2. Multinomial regression analysis was used to characterize resistance effect on death, failure, and loss-to-follow-up, adjusting for key variables. Results: The initial cohort (n = 480) was 52% (n = 251) female, median age 8 years, median CD4% 31%, 79% (n = 379) on zidovudine/abacavir + lamivudine + efavirenz/nevirapine for median 2 years. Of these, 31% (n = 149) failed at timepoint 1. Genotypes at timepoint 1, available on n = 128, demonstrated 93% (n = 119) extensive resistance, affecting second line. Of 128, 22 failed at timepoint 2, 17 died, and 32 were lost to follow-up before timepoint 2. Having >5 resistance mutations at timepoint 1 was associated with higher mortality [relative risk ratio (RRR) = 8.7, confidence interval (CI) 2.1 to 36.3] and loss to follow-up (RRR = 3.2, CI 1.1 to 9.2). Switching to second line was associated with lower mortality (RRR <0.05, CI <0.05 to 0.1) and loss to follow-up (RRR = 0.1, CI <0.05 to 0.3). Conclusion: Extensive resistance and limited switch to second line in perinatally infected Kenyan CALWH failing first-line ART were associated with long-term failure and mortality. Findings emphasize urgency for interventions to sustain effective, life-long ART in this vulnerable population. Abstract : Supplemental Digital Content is Available in the Text.